Eolation dynamics in the shore of artificially impounded bodies (by the example of Bratsk water reservoir, Russia) - Khak, V.; Kozyreva, E.; Trzhcinsky, Yu. B. (Bulletin of the Geological Society of Greece, 2007)
The process of eolation in the near-shore area of the Bratsk water reservoir results in the landscape changes and may lead to abrasion process activation. The eolation dynamics factors are water level and wind conditions. The eolation shows a cyclical pattern that is primarily related to the duration of low stand of level. The eolation processes that differ in sedimentation rate, water level and morphology of eolian relief forms ranging from mere sand blowing to travelling dunes have been phased in studies of the sections of dune sand deposits. The topography model of index plot Rassvet that makes it possible to scale the process of eolation and to know some regular trends and mechanisms of its development has been constructed as result of eolation dynamics research.